Ziemiaństwo a uprzemysłowienie Galicji na przełomie XIX i XX w. (do 1918 r.) - Kargol, Tomasz (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
Article presents the attitude of gentry to the industrialization of Galicia in the second half of the 19th century and the beginning of the 20th century. This problem hugs the commitment in non-agricultural sectors of industry territorial capital, the industrialization territorial properties, functioning the chosen of properties and institutions as well as works of gentry at industrial organizations. The traditional branches of food industry in territorial properties predominated: the distillery, the breweries, the flour-mills, basing on own materials of earthly goods as well as wood industry. Few aristocrats, as count Andrew Potocki from Krzeszowice, duke Andrew Lubomirski from Przeworsk and count Eduard Mycielski, invested in heavy industry (mining, metallurgy) and machine. Devoid industrial institutions properties in Galicia overweighed, or be possessing only distilleries, mills, sawmills brick-yards. The activity of gentry did not influence on industrialization of country. Many landowners was however engaged in activity of organization popularizing the industrialization or it sat down in powers of joint-stock companies. Showed on this field with special activity duke Andrew Lubomirski.